The perceptions of Malawians living in Gauteng, South Africa, on the contributions of indigenous Malawian tribes' cultural practices in HIV infection in Malawi. - Munlo, Juliana (My University, 2011)
It is well known that the human immunodeficiency virus (HIV) and acquired immunodeficiency syndrome (AIDS) have affected millions of people throughout the world and continues to affect people on a day to day basis. In Africa, sub-Saharan Africa is the most affected. Malawi, one of the poorest countries in sub-Saharan Africa is no exception to the growing trend and severity in HIV prevalence (Kalipeni& Ghosh, 2006).Like many countries in Africa, cultural practices in Malawi have been criticised as contributing to the spread of HIV and AIDS (Mwale, 2008). In recent years it has been recognised that in order to understand the spread of HIV and AIDS it is imperative to address the economic, social, cultural and political issues that lead to the contraction and spread of the virus. Hence there is a growing realisation that more effective prevention strategies in response to HIV and AIDS should focus on traditional, cultural, medical and political beliefs and practices as well as perceptions of individual risk to HIV and AIDS (Lwanda, 2005).The proposed research seeks to explore the perceptions of Malawians in the role and implications that cultural practices play in promoting HIV infections in Malawi. A sample of 17 people representing both genders from three tribes, namely the Yao, Tumbuka and Chewa participated in the study. Participants were purposively selected on their knowledge of cultural practices and in their being members of the tribe that was investigated. The research study was qualitative and a case study research design was applied. Data was analysed using thematic content analysis. The findings were therefore organised according to themes. The findings were that a number of cultural practices of the Tumbukas, Chewas and Yaos play a role in HIV and AIDS infections. Some of the cultural practices that were identified included wife inheritance, polygamy, initiation ceremonies, the practice of fisi(hyena), the practice of kulowafumbi(wiping of dust) and traditional marriages. The study found that cultural practices accompanied by lack of education, poverty, gender inequalities, lack of condom use and peer pressure among the youth promotes risky behavior that often leads to HIV transmission and prevents behavioural change. It was identified that it would be beneficial to educate elders of the community and influential people about HIV so that they could teach community members about the link between HIV and AIDS and cultural practice, and to find alternative ways to ensure that the cultural practice is safer, such as encouraging people to test before they practice wife inheritance. This study hopefully has the potential of contributing to knowledge and awareness in the fields of social development and social work on the role that cultural practice plays in promoting risky behaviour,which leads to contracting HIV infection among the Chewa, Tumbuka and Yao tribes. These findings could be useful in the creation of cultural-specific intervention programmes that are aimed at curbing HIV infection in Malawi and in many African countries where similar cultural practices are practiced.
Keywords: Culture; Cultural practices; HIV and AIDS; Poverty; Gender inequality